2013
DOI: 10.1007/s12010-013-0586-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Growth Conditions for the Expansion of Porcine Mesenchymal Stem Cells on Microcarriers in Stirred Cultures

Abstract: The extensive use of mesenchymal stem cells (MCS) in tissue engineering and cell therapy increases the necessity to improve their expansion. Among these, porcine MCS are valuable models for tissue engineering and are classically expanded in static T-flasks. In this work, different processes of stirred cultures were evaluated and compared. First, the effect of glucose, glutamine, antioxidant, and growth factors concentrations on porcine MSC expansion were analyzed in a suitable medium by performing kinetic stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 58 publications
2
22
0
Order By: Relevance
“…In fact, normal cells especially stem cells are highly sensitive to ROS, thus the adding of antioxidant agent in culture medium is useful to reduce ROS‐mediated damage in cell systems such as neuronal cell systems . Several studies showed that the presence of antioxidant compounds in the basal medium, such as ascorbic acid, thioctic acid, β‐mercaptoethanol and sodium selenium, has positive effects on MSCs growth …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, normal cells especially stem cells are highly sensitive to ROS, thus the adding of antioxidant agent in culture medium is useful to reduce ROS‐mediated damage in cell systems such as neuronal cell systems . Several studies showed that the presence of antioxidant compounds in the basal medium, such as ascorbic acid, thioctic acid, β‐mercaptoethanol and sodium selenium, has positive effects on MSCs growth …”
Section: Resultsmentioning
confidence: 99%
“…To avoid cell aggregation, some studies proposed controlling operating parameters such as agitation rate, cell density, and addition of carriers . Sometimes, due to the smooth surface of microcarriers such as glass microcarriers and Cytodex, MSCs cannot attach firmly and may detach and be washed away during medium changes . In addition, those microcarriers cannot be digested in the human body .…”
Section: Introductionmentioning
confidence: 99%
“…The impact of glutamine has been studied less extensively than that of glucose. Ferrari et al observed an increase in peak cell density by approx 25 % when adding of 2 to 6 mM of glutamine [84]. Schop et al concluded from their studies that glutamine has no importance as an energy source for hMSCs [93].…”
Section: Characteristics Of Mscs and The Influence Of The Engineeringmentioning
confidence: 99%
“…Due to the importance of hyperglycemia in vivo and the hypothesis, that high glucose could be deleterious to stem cell therapy, the impact of glucose on proliferation, potential for differentiation, and other physiological effects have been studied intensively. Glucose concentration in basal media has been shown to have both positive and negative impacts on MSC growth [47,[82][83][84][85][86][87][88][89][90][91][92][93]. It is beyond the scope of this chapter to discuss the various effects in detail but certain findings are presented below to highlight the complexity of this topic:…”
Section: Characteristics Of Mscs and The Influence Of The Engineeringmentioning
confidence: 99%
See 1 more Smart Citation